You are apparently being asked to identify the equations that result when
... 2x - 3y = 1
remains unchanged, and the first equation is replaced by
... (5x +2y) +(2x -3y) = (3) +(1).
The sum will be
... x(5+2) + y(2-3) = 3+1
... 7x - y = 4
So, the two equation in the system will now be
... 7x - y = 4
... 2x - 3y = 1
This description of the system corresponds to choice ...
... a. Show that the solution to the system of equations 7x - y = 4 and 2x - 3y = 1 is the same as the solution to the given system of equations.